Estudio del trayecto descendente del nervio bucal en individuos adultos - Alves, Nilton [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2009)
The knowledge of the buccal nerve anatomy is of fundamental importance not only for the anesthesia but also for a safe intervention in the retromolar area. The aim of this work was to study its trajectory, in the area where it is related to the anterior margin of the ramus of the mandible, therefore providing important data for a safe intervention in the region. In this study we used 10 hemi-heads from male and female adults, from different ethnic groups. They were fixed in formol, and belong to the Anatomy Laboratory at the Faculty of Dentistry in Araraquara UNESP. These hemi-heads were dissected by lateral access, preserving the buccal nerve in its trajectory related to the anterior margin of the ramus of the mandible until its penetration in the buccinator muscle. Next, we desinserted the masseter muscle so that all the ramus of the mandible were exposed. Then, the following measurements were carried out: from the base of the mandible until the buccal nerve and from the base of the mandible until the apices of the mandibular coronoid process. These measurements were accomplished with a Mitutoyo CD-6 CS digital paquimeter. The following average values were obtained: 32.26 mm (to the left side) and 32.04 mm (to the right side), from the base of the mandible until the buccal nerve and 59.09 mm (to the left side) and 58.95 mm (to the right side) from the base of the mandible until the apices of the coronoid process. We have concluded that normally, the buccal nerve crosses the anterior margin of the ramus of the mandible in an area which is above the superior half of the ramus of the mandible and also that the interventions in the retromolar region do not offer great risks of injury in the buccal nerve.
Study of descendent course of buccal nerve in adults individuals
Keywords: Buccal nerve; Nerve anatomy; Nerve trajectory; Retromolar area